Primerjava besedil dementnih in zdravih starostnikov - Trojar, Valerija (Jezik in slovstvo, 2007)
Dementia is a group of disorders affecting the cognitive, emotional, behavioural and physical capacities, bearing an influence on communicative andspeaking abilities. Changes affecting the elderly population also influenceboth their communicative and speaking abilities. The author of the present article aims to discover the differences between the texts produced onthe basis of pictures by both, the elderly suffering from dementia, and the healthy group of elderly persons over the age of 65, and to test the method ofpicture-based text analysis. The texts are compared on the basis of their length and duration, the informative value of the text, the manner of naming, the macro-structure of the text, and their performative level. The greatest differences are observed in the number of the aforementioned cause/effect relations, the distribution of the Slovene verb biti (- to be in English) compared to all other verbs used, immediate repetition of words and self-corrections. The main difference between the texts produced by the elderly with and without dementia is that those suffering from dementia are less able to compensate for the deficiencies weakening their speaking ability with adequate compensatory strategies.
Keywords: demenca; dementia; nevrolingvistika; skladnja; Slovene; slovenščina; syntax